2020
DOI: 10.3390/ijerph17134806
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Classroom Program of Physiotherapy among Spanish Adolescents with Back Pain: A Collaborative Study

Abstract: Background: The prevalence of back pain in adolescents is steadily increasing, with negative repercussions on students’ social and academic life. This study sought to improve the ergonomics and musculoskeletal health of adolescents in secondary school by implementing physiotherapy actions within the educational context. Methods: A qualitative collaborative action research approach was used, comprising 49 students, 9 teachers, 11 family members, and 9 physiotherapists. Workshops on ergonomics, stretchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
8
0
3
Order By: Relevance
“…Physiotherapy treatment for LBP generally includes a combination of mobilization, massage, and different manual therapy techniques [ 4 , 5 ], combined with active therapies such as motor control exercise [ 6 , 7 , 8 ], Pilates exercise [ 9 ], and others [ 10 ]. Some authors, analyzed different approaches offered for the treatment of back pain, suggesting the use of massage as a complement to other therapies such as mobilization or exercise [ 11 ]. Several studies reported the effectiveness of this techniques to certain degree, especially in the short term [ 3 , 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy treatment for LBP generally includes a combination of mobilization, massage, and different manual therapy techniques [ 4 , 5 ], combined with active therapies such as motor control exercise [ 6 , 7 , 8 ], Pilates exercise [ 9 ], and others [ 10 ]. Some authors, analyzed different approaches offered for the treatment of back pain, suggesting the use of massage as a complement to other therapies such as mobilization or exercise [ 11 ]. Several studies reported the effectiveness of this techniques to certain degree, especially in the short term [ 3 , 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This topic is also important because associations between adolescent and adult LBP has been observed [ 5 , 6 ]. Although most of the studies in adults have analyzed LBP, evidence suggests that the importance of cervical pain (CP), defined as pain experienced in the region of the cervical spine, between the boundaries of C1-C7 and across the posterior aspect of the neck [ 2 , 7 ], and thoracic spine pain (TSP), defined as pain experience in the region of the thoracic spine, between the boundaries of T1-T12 and across the posterior aspect of the trunk [ 7 ], should also be analyzed during adolescence because the incidence and prevalence of pain in different areas of the spine are high at this growth stage [ 1 , 2 , 7 , 8 , 9 ]. Therefore, spinal pain (SP) as a global concept that encompasses CP, TSP and LBP, defined as pain perception in the neck or back that could be influenced by spine bones, ligaments, muscles and tendons as active and passive structures [ 10 ] but also by more central structures [ 11 , 12 ], could be the key during adolescence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scoping review, 32 studies included information about adolescents’ understanding of and knowledge about musculoskeletal health information. Some of the qualitative studies focused on the target groups’ experiences in understanding health information provided by healthcare personnel 40 44 47 50 54. For example, one study focused on adolescents’ understanding of information about scoliosis during a consultation 40.…”
Section: Resultsmentioning
confidence: 99%